Characterization of Circulating Clostridium difficile Strains, Host Response and Intestinal Microbiome in Hospitalized Children With Diarrhea. Issue 3 (March 2020) - Lees, Emily Ann; Carrol, Enitan D.; Ellaby, Nicholas A. F.; Roberts, Paul; Corless, Caroline E.; Lenzi, Luca; Darby, Alistair; O'Brien, Sarah J.; Cunliffe, Nigel A.; Turner, Mark A.; Miyajima, Fabio; Pirmohamed, Munir
Abstract : Background: Clostridium difficile is capable of causing severe enterocolitis in adults. The significance of toxin-producing C. difficile in children with diarrhea is unclear and practice differs on whether to institute treatment. We aimed to characterize the microbiome in relation to the presence of C. difficile and co-infection with other pathogens and to describe host response to infection. Methods: Participants were children with acute diarrhea, 0–16 years of age, from whom stool samples had been submitted to the hospital laboratory for routine microbiology/virology. Convenience sampling was used for 50 prospective and 150 retrospective samples. No participants were treated for C. difficile . Rates of culture positivity for C. difficile, presence of toxin and PCR-ribotype were compared between age groups. Presence of other potential pathogens, comorbidities and complications were recorded. Microbiotal diversity was measured by 16S profiling. Results: Nineteen of 77 (25%) children <2 years of age and 13 of 119 (11%) children >2 years of age were C. difficile positive, of whom 10 (53%) and 9 (69%), respectively, carried toxigenic strains. Increased Shannon diversity was seen in children carrying C. difficile, with altered milieu. Presence of C. difficile was not associated with adverse clinical outcomes. In stools containing both Norovirus and C. difficile, there was increased relative abundance of verrucomicrobia. Conclusions: Children with diarrhea regularly carried toxigenic and non-toxigenic strains of C. difficil e, demonstrating enhanced microbiotal diversity, and change in milieu, without apparent morbidity. This unexpected finding is contrary to that seen in adults with C. difficil e disease. Abstract : Supplemental Digital Content is available in the text.